1986
DOI: 10.1001/archderm.1986.01660220057014
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Morphometric and Immunohistochemical Analysis of Cutaneous Lymphomas and Benign Lymphocytic Infiltrates of Skin

Abstract: Our combined ultrastructural, immunohistochemical, histologic, and clinical studies over the past five years have allowed us to compile diagnostic criteria useful in the evaluation of cutaneous lymphomas. As a group, mycosis fungoides (MF) patients could be distinguished from those with benign disorders of skin using ultrastructural morphometry (mean form factor and perimeter values), but with some overlap between groups. Another approach, the ultrastructural histogram method, however, clearly separated MF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Other authors have used combinations of morphology and immunostaining, mostly by electron microscopy, in order to achieve better morphological details or to ensure that the cells analysed corresponded to T-lymphocytes 1214. Although important for scientific purposes, the use of ultramicroscopy and immunoelectron microscopy is by no means feasible in routine diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have used combinations of morphology and immunostaining, mostly by electron microscopy, in order to achieve better morphological details or to ensure that the cells analysed corresponded to T-lymphocytes 1214. Although important for scientific purposes, the use of ultramicroscopy and immunoelectron microscopy is by no means feasible in routine diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Immunophenotyping with leukocyte monoclonal antibodies is helpful to detect monoclonal B-cell proliferation by light chain restriction. 4,5 However, a discrete monotypic B-cell infiltrate can be masked by a dense reactive infiltrate. 6 Molecular analysis of lymphoid gene rearrangements by Southern blot analysis has proved to be useful for the detection of clonal populations and the determination of the lineage of lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the proliferation was either nodular (periadnexal or perivascular) or diffuse, the upper part of the derm (Grenzzone) remained in tact except in case 6 and no epidermotropism was noted. However, Payne et al [30] recently reported non-MF/SS peripher al T cell lymphomas with epidermotropism.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of the proliferation, polyclonal staining of in tracellular immunoglobulins and blood eosinophilia have a limited value as criteria of pseudolymphomas since there is sometimes an exuberant host response in non-MF/SS Tcell lymphomas (case 1) [13]. Similar ma ture Tcell phenotype may be present both in pseudolymphomas and Tcell lymphomas [48,49] although the immunological characteristics of benign infiltrates are usually more heterogeneous [30], The T cell receptor gene study may thereby be a major tool for early differentiation between Tcell lymphomas and pseudolymphomas [13].…”
Section: Discussionmentioning
confidence: 99%